Discursos eleitorais de PT e PSDB nos programas de governo e debates televisivos: ideologia, estratégias e pragmatismo - Vizoná, Amanda (2019)
This thesis has been developed based upon the hypothesis that PT and PSDB, the main farsided Brazilian political parties in the last two decades, have made an ideological centripetal move, approaching political agendas that used to distinguish them. This move explains the weakening of the party-elector bounding and the end of the political polarization leading, thus, to the electoral defeat of both sides in 2018. In order to evaluate this hypothesis this article considers political parties analytical theories and their strategies and ideological preferences: the Rational Choice theory, which considers political parties as pragmatics vote-seeking institutions, and the Saliency theory, which considers party documents and official speeches as ideological propagandas capable to connect and attract supporters. Thus, this present article intends to evaluate the political party positioning through the cross-analysis of the govern program and the speech during the electoral televised debates. To do so, the speech sentence analysis method was used in order to fit such sentences into the categories designed by the “Manifesto Research on Political Representation” (MARPOR). After measuring the consentaneity between party documents and the speech during the electoral debates, such as the parties’ strategies to communicate them to the electors, this article contributes to the campaign strategy literature and points out that PT and PSDB are very much alike, in despite of what they allege.